La enseñanza de la historia y la geografía dentro de las reformas educativas en secundaria de 1973-2006 - Guzmán Alvarado, Yajaira (Universidad Michoacana de San Nicolás de Hidalgo, 2012)
The history of the education in Mexico is a topic that it has been analyzed very little. In comparison with other studies, the historiography of the education is very limited and inside the little thing that he/she has been dedicated we are with which the historical study of the teaching of the history and of the geography in secondary in Mexico is still smaller. Inside the educational reformations it is of great importance the paper of the teaching of the history and of the geography; both are part of the sphere of the social sciences and I eat matters of social order they have been dedicated less time and effort that to the functional subjects as they are it mathematical and Spanish that are generally those that more emphasis is granted. What this project outlines is thoroughly analyzing the educational main reformations that have been made in the last forty years, from the Federal Plan of Education rushed in 1973 until the last educational reformation implemented in the year of 2006, but focused to the teaching of the history and of the geography.

La historia de la educación en México es un tema que se ha analizado muy poco. En comparación con otros estudios, la historiografía de la educación es muy limitada y dentro de lo poco que se le ha dedicado nos encontramos con que el estudio histórico de la enseñanza de la historia y de la geografía en secundaria en México es todavía menor. Dentro de las reformas educativas es de gran importancia el papel de la enseñanza de la historia y de la geografía; ambas forman parte de la esfera de las ciencias sociales y como materias de orden social se les ha dedicado menos tiempo y esfuerzo que a las asignaturas funcionales como lo son matemáticas y español que generalmente son a las que más énfasis se les otorga. Lo que este proyecto plantea es el analizar a fondo las principales reformas educativas que se han hecho en los últimos cuarenta años, desde el Plan Federal de Educación lanzado en 1973 hasta la última reforma educativa implementada en el año de 2006, pero enfocadas a la enseñanza de la historia y de la geografía.
Instituto de Investigaciones Históricas. Facultad de Historia. Maestría en Enseñanza de la Historia
Keywords: info:eu-repo/classification/cti/4; IIH-M-2012-0010; Geografía; Reforma educativa; Educación secundaria; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2506